Fire fighting robot - Vadivell, Loganathan; Ahmad, Anita; Buyamin, Salinda; Ibrahim, Sallehuddin (Penerbit UTHM, 2020)
Fire-fighting is an important but dangerous occupation. A fire-fighter must be able to put out fire quickly and safely. This is a common way to prevent fatalities and further damages. So, technology has done its part by bridging up the gap between fire fighters and machineries. So, a robot is invented in order to combine both man kind and technology [1]. Fire Fighting Robot is designed to put out a fire, before it reaches out of control. Robot with these fire-handling abilities is a great advantage to replace fire extinguishers [2]. Water-based robot will be an advantage for users to refill the tank as it goes empty. Users can fill up water and keep the robot in a safe position. Water is a basic non-chemical liquid which will not experience any expiry or damage or corrosion. This invention would be a great contribution to mankind in order to ease their work and minimize the risk during fire put out.